ANALISIS YURIDIS TERHADAP UNSUR-UNSUR NOODWEER DALAM PUTUSAN PENGADILAN NEGERI BANDUNG NOMOR 162/PID.B/2021/PN.BDG - Monika Romauli Manurung; R. Rahaditya (Jurnal Hukum Adigama, 2022)
The idea of noodweer is that the act is executed on the idea of the usage of the proper andright pressure in order that there's no other dif erent choice, which may be used apartfrom committing an act that violates the regulation. The act ought to meet importantpoints, namely: there became a right away assault wherein at once threatened and inopposition to the regulation. The assault intentionally geared toward the body, politenessand possessions belongs to himself or others. So far, withinside the case of crook acts ofpersecution in particular, the utility of the precept of pressured protection is regularlynow no longer according with the concept in essence. In addition, the pressuredprotection is likewise substantially stimulated with the aid of using the continuedproduction of the case, how the proof is presented, and the way they of ers felonyconsiderations withinside the absence of maximal proof, it's miles clean that the chooseadditionally did now no longer behavior a seek associated with the that means of theessence of a pressured protection. The technique in this case is descriptive. This studiesbecame performed thru regulation normative approach, with the aid of using analyzingthe legal guidelines and all informations that is associated with this example.